Influence Of Oil Palm Fiber And Steel Fiber Inclusion On Properties Of Concrete - Khor, Cheng Yi (Universiti Sains Malaysia, 2021)
Empty fruit bunches (EFB) are the waste that is left after the fruit of oil palm is extracted and the oil is being processed. Oil Palm Fiber (OPF) can be obtained from the vascular bundle of EFB. Inclusion of OPF into the concrete mix as partial replacement for Steel Fiber (SF) in fiber reinforced concrete can help to reduce the waste produced for a greener environment. This research studies the influence of the inclusion of OPF and SF to the properties of concrete. OPF of length 30-50mm and SF with a length of 10mm-16mm and diameter of 0.2mm is used in this research. Six (6) different batches of mixes were prepared, namely Mix A (control), Mix B (1% SF, 0% OPF), Mix C (0.75% SF, 0.25% OPF), Mix D (0.5% SF, 0.5% OPF), Mix E (0.25% SF, 0.75% OPF) and Mix F (0% SF, 1.0% OPF). The properties of the fresh concrete, which is the workability and hardened concrete, which is the density, compressive strength, flexural strength, splitting tensile strength and direct tensile strength were assessed using different methods. The results obtained show that the inclusion of fiber to concrete mix reduced the workability of the concrete mix gradually as the fluidity of concrete mix is decreased by the fiber. Besides that, Mix B with 1.0% of SF inclusion shows increase in mechanical properties while Mix F with 1.0% of OPF inclusion shows reduction in mechanical properties compared to plain concrete. On the other hand, Mix C with combination of 0,75% of SF and 0.25% OPF shows increase in mechanical properties compared to plain concrete but cannot achieve the same as to Mix B.